Accessory optical device for the Heidelberg retina angiograph ( HRA classic ) to perform angiography of the vitreous cavity and the anterior eye segment - Mennel Stefan; Schwendinger Rudolf; Hausmann Norbert; Peter Silvia (Indian Journal of Ophthalmology, 2007)
The Heidelberg retina angiograph ( HRA) classic enables fluorescein angiography (FA) and indocyanine green angiography (ICG-A) of the retina and choroid. The goal of this study was to design an accessory device to adapt the HRA classic for application on structures anterior to the retina. The optical device consisted of a cylindrical two-piece plastic frame holding a magnifying lens commonly used with the indirect ophthalmoscope. A 60-diopters lens was inserted in this frame to enable the angiography of the anterior segment. A less strong lens of 30 diopters was used for the visualization of pathologic findings in the vitreous cavity. We designed an easy-to-use and low-cost device to adapt the HRA classic for angiography of the fundus, vitreous cavity and anterior segment in the same session and without delay. FA and ICG-A images of two patients with rubeosis iridis and of one patient with choroidal melanoma are described.